Três planos em três tempos: transformação urbana e modernização cidade de João Pessoa - Araújo, Milena Lima de (2007)
The present paper argues the process of urban transformation and modernization of the city of João Pessoa, current capital of the Paraíba, in the period of 1858 to the 1940. This period is marked, in its great majority, for accomplishments of the public power, these mark the road structure radically, the infrastructure and the urban landscape of the capital. Although to be a city of few dimensions and still colonial João Pessoa was not outside of the panorama of Brazilian urban transformations, as the cities of Rio de Janeiro, Recife and São Paulo. The research focuses on the study of the reflected alterations of the space in the modernization of the urban infrastructure, of the public spaces and the architecture, using as analysis support the iconography of the city. The analyses will be carried through from three plans Henrique B. Rohan (1858), Saturnino de Brito (1913) e Nestor de Figueiredo (1932) complemented for a retrospective urban of the city 9 plants of the city of the years of 1585 up to 1940, and for documentation photographic.